2020
DOI: 10.12788/jhm.3370
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Increased Pediatric Reutilization After a Postdischarge Home Nurse Visit

Abstract: BACKGROUND: The Hospital to Home Outcomes (H2O) trial was a 2-arm, randomized controlled trial that assessed the effects of a nurse home visit after a pediatric hospital discharge. Children randomized to the intervention had higher 30-day postdischarge reutilization rates compared with those with standard discharge. We sought to understand perspectives on why postdischarge home nurse visits resulted in higher reutilization rates and to elicit suggestions on how to improve future interventions. METHODS: We soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Updated literature search for potential qualitative studies from March 2020 to October 2021 identified 5 additional studies that were considered eligible (Supplementary file 4). A total of thirteen qualitative studies, 9,10,[23][24][25][26][27][28][29][30][31][32][33] were included. Details of literature search and study selection are presented in Figure 2.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Updated literature search for potential qualitative studies from March 2020 to October 2021 identified 5 additional studies that were considered eligible (Supplementary file 4). A total of thirteen qualitative studies, 9,10,[23][24][25][26][27][28][29][30][31][32][33] were included. Details of literature search and study selection are presented in Figure 2.…”
Section: Study Selectionmentioning
confidence: 99%
“…Individual interviews Thematic analysis Registered nurses (n = 7), primary care physicians (n = 9), paramedics (n = 3), advanced practice registered nurses (n = 3). Riddle 2020, US 32 To elicit suggestions for improving a nurse visit intervention for reducing hospital readmission.…”
Section: Misra-hebert 2021 Us 29mentioning
confidence: 99%
See 1 more Smart Citation
“…For pediatric patients, parent and guardian (hereafter referred to as "parents") communication with clinicians impacts patient safety, parent experience, and hospital utilization (9,(13)(14)(15). Unfortunately, communication challenges not only exist, but the awareness of these problems among clinicians is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the Journal of Hospital Medicine, Riddle et al 3 explored the perspectives of key stakeholders to understand the factors driving increased reutilization after postdischarge home visits in the H2O trial and obtained feedback for improving potential interventions. The investigators used a qualitative approach that consisted of telephone interviews with 33 parents who were enrolled in the H2O trial and in‐person focus groups with 10 home care RNs involved in the trial, 12 hospital medicine physicians, and 7 primary care physicians (PCPs).…”
mentioning
confidence: 99%